If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4h + -6 = 10n Reorder the terms: -6 + 4h = 10n Solving -6 + 4h = 10n Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4h = 6 + 10n Combine like terms: -6 + 6 = 0 0 + 4h = 6 + 10n 4h = 6 + 10n Divide each side by '4'. h = 1.5 + 2.5n Simplifying h = 1.5 + 2.5n
| -12m-8=70 | | 0.16666666666(12-6x)=5(x+4) | | 0.33333333333(6y-9)=-2y+13 | | 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) | | 28-2x=3x+18 | | .03=.14x+.05-05x | | 8+.09m=90 | | G(2)=5-7+2 | | b/0.8=12.6 | | -6m-13=74 | | 6x^2-54x/x-9•7x/6x | | -7.1=2.9-5y | | 10=1.25*p | | g/3.2=4.7 | | g/2=0.5 | | 4r^2=34-10r | | 4(24)=4(20)+4(4) | | (5x+7)+(4x-18)+(3x+2)=x | | 4q+8q+7q-7= | | 9x+x=79 | | 2(6k-7)+6(-3k+1)=22 | | 175+g=118 | | 4y=3(y-5)-2 |